2021
DOI: 10.3389/fphys.2021.715443
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects on Brain Micro-Environment by Caloric Restriction in Alleviating Neurodegenerative Diseases and Brain Aging

Abstract: Aging and neurodegenerative diseases are frequently associated with the disruption of the extracellular microenvironment, which includes mesenchyme and body fluid components. Caloric restriction (CR) has been recognized as a lifestyle intervention that can improve long-term health. In addition to preventing metabolic disorders, CR has been shown to improve brain health owing to its enhancing effect on cognitive functions or retarding effect on the progression of neurodegenerative diseases. This article summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 190 publications
(200 reference statements)
1
7
0
Order By: Relevance
“…92 Mild stress due to dietary restriction has shown benefits for lifespan, health span and brain health. [93][94][95] Our work demonstrates a similar phenomenon in the context of neurodegenerative disease and dendrite repair. Previous work has shown that activating the integrated stress response is beneficial in HD and ALS models.…”
Section: Moderate Stressors Have Been Associated With Benefits For Or...supporting
confidence: 67%
“…92 Mild stress due to dietary restriction has shown benefits for lifespan, health span and brain health. [93][94][95] Our work demonstrates a similar phenomenon in the context of neurodegenerative disease and dendrite repair. Previous work has shown that activating the integrated stress response is beneficial in HD and ALS models.…”
Section: Moderate Stressors Have Been Associated With Benefits For Or...supporting
confidence: 67%
“…Indeed, reduced ECM synthesis is thought to contribute to exacerbated age-associated deficits in wound healing 41 and skin quality 42 concomitant with ageing. Saying this, reducing ECM deposition has been shown to contribute to the anti-hypertensive 43 and neuroprotective 44 effects of CR. Ultimately, how CR-mediated alterations in ECM organisation might alter sarcopenia and overall muscle health should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction (CR) extends the lifespan, improves health, and slows ARHL progression in older adults [101]. Furthermore, CR was shown to reduce the incidence of obesity, diabetes, and tumors [102]; protect neurons from neurodegenerative diseases [103]; and decrease inflammation and oxidative damage in aged brains, hearts, and livers in animal models [104]. Several studies have attempted to elucidate whether CR or dietary restriction (DR) can protect against age-related hearing loss in animal models [44,105,106].…”
Section: Low Sugar and Caloric Restriction Dietmentioning
confidence: 99%